Nitrogen rather than water availability limits aboveground primary productivity in an arid ecosystem: substantial differences between grasses and shrubs - Carbonell-Silletta, Luisina; Scholz, Fabian Gustavo; Burek, Antonella; Diaz Villa, Virginia; Cavallaro, Agustín; Askenazi, Javier Oscar; Arias, Nadia Soledad; You Hao, Guang; Goldstein, Guillermo; Bucci, Sandra Janet (Wiley, 2024)
Changes in water and nitrogen availability can affect the structure and function of arid ecosystems. How these resources affect aboveground primary productivity (ANPP) remains far from clear. We examined the N and water limitation of ANPP from the species to the community level and the response of ANPP to annual precipitation in a Patagonian steppe. We conducted a 7-year field experiment with water addition (+W), nitrogen addition (+N) and +NW. Destructive methods for grasses and allometric relationships for shrubs were used to assess ANPP and vegetation indices (NDVI and MSAVI2) to estimate community ANPP. An increase in ANPP of one grass species (Papposstipa humilis) and a decrease of the grass Poa ligularis under +N were observed. Some shrub species exhibited mortality under nitrogen addition. Nitrogen exerted a positive effect on grass ANPP and amplified the sensitivity of grass ANPP to annual precipitation. However, +N had not effects on the shrub ANPP and shrub ANPP-precipitation relationship. Water addition by itself had no effect on ANPP for either shrubs or grasses. However, shrubs responded positively to an unusually wet year regardless of treatment and were also more sensitive to changes in annual precipitation than grasses. Total ANPP increased significantly in +N relative to the C and +W but without changes in the sensitivity to annual precipitation. The results suggest that the responses of grasses and shrubs to water inputs are driven by soil moisture redistribution and rooting depth and that grass and community ANPP are more limited by N than by water.